2021
DOI: 10.1002/cssc.202102217
|View full text |Cite
|
Sign up to set email alerts
|

Identifying UiO‐67 Metal‐Organic Framework Defects and Binding Sites through Ammonia Adsorption

Abstract: Ammonia is a widely used toxic industrial chemical that can cause severe respiratory ailments. Therefore, understanding and developing materials for its efficient capture and controlled release is necessary. One such class of materials is 3D porous metal-organic frameworks (MOFs) with exceptional surface areas and robust structures, ideal for gas storage/transport applications. Herein, interactions between ammonia and UiO-67-X (X: H, NH 2 , CH 3 ) zirconium MOFs were studied under cryogenic, ultrahigh vacuum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 95 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…The C–H···N hydrogen bonds are formed by electrostatic attractions between the lone pair electrons of the nitrogen atom and the H atoms of acetylene molecules. Similarly, electrostatic attractions between the H atoms of ammonia and the electron-rich π-system of a neighboring acetylene molecule give rise to N–H···π hydrogen bonds. These C–H···N and N–H···π interactions play a crucial role in determining the structure and dynamics of the acetylene:ammonia (1:1) co-crystal.…”
Section: Resultsmentioning
confidence: 99%
“…The C–H···N hydrogen bonds are formed by electrostatic attractions between the lone pair electrons of the nitrogen atom and the H atoms of acetylene molecules. Similarly, electrostatic attractions between the H atoms of ammonia and the electron-rich π-system of a neighboring acetylene molecule give rise to N–H···π hydrogen bonds. These C–H···N and N–H···π interactions play a crucial role in determining the structure and dynamics of the acetylene:ammonia (1:1) co-crystal.…”
Section: Resultsmentioning
confidence: 99%
“…82 To determine if this process occurs, we compare the line shape of ν(OH) free before, during, and after CD 3 CN exposure (Figure S18). The ν(OH) free line shape, reported to be a combination of both μ 3 -OH and isolated H 2 O species, 22,30 is initially symmetric and becomes slightly asymmetric following CD 3 CN desorption (blue trace, Figure S18). The induced asymmetry suggests that CD 3 CN successfully displacing a small fraction of H 2 O ligands.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…700 K. 25 Dehydroxylation occurs by heating UiO-67 between ca. 500 and 600 K. 22,25 It has additionally been reported that under ambient conditions, thermally activated UiO-66 MOFs have a higher density of defect sites. 26,27 Since UiO-66 and UiO-67 share identical nodal structures and differ primarily by the identity of the linker molecule, 28 thermal activation of UiO-67 should show a similar response.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations